2018
DOI: 10.5489/cuaj.5405
|View full text |Cite
|
Sign up to set email alerts
|

Trends and disparities in the use of neoadjuvant chemotherapy for muscle-invasive urothelial carcinoma

Abstract: Introduction: Neoadjuvant chemotherapy (NAC) prior to radical or partial cystectomy is considered the standard of care for eligible patients with muscle-invasive urothelial carcinoma. Despite guideline recommendations, adoption of NAC has historically been low, although prior studies have suggested that use is increasing. In this contemporary study, we examine trends in the use of NAC and explore factors associated with its receipt. Methods: We identified patients in the National Cancer Database who underwent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 27 publications
4
33
0
Order By: Relevance
“…28 Indeed, a recently published manuscript found that neoadjuvant chemotherapy is used more frequently in patients with a higher clinical T-stage. 29 benefit would be several millions of dollars per year. However, we did observe a slightly higher readmission rate, which can offset the potential benefit of shorter stays.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 Indeed, a recently published manuscript found that neoadjuvant chemotherapy is used more frequently in patients with a higher clinical T-stage. 29 benefit would be several millions of dollars per year. However, we did observe a slightly higher readmission rate, which can offset the potential benefit of shorter stays.…”
Section: Discussionmentioning
confidence: 99%
“…Potentially, the introduction of neoadjuvant chemotherapy also resulted in patients with more advanced disease undergoing RC, reducing the survival benefit due to selection bias . Indeed, a recently published manuscript found that neoadjuvant chemotherapy is used more frequently in patients with a higher clinical T‐stage . It is possible that other variables than the ones analyzed may have contributed in part to the improved BC outcome as well.…”
Section: Discussionmentioning
confidence: 99%
“…Hopefully, many studies have reported an improvement in the use of NAC, and the low uptake worldwide seems to decrease over time but still remains too low. 3944 The results of the last meta-analysis published confirmed the superiority of NAC and showed an 8% absolute improvement in survival at 5 years with a number needed to treat of 12.5. 45…”
Section: Chemotherapy Typementioning
confidence: 91%
“…A notable aspect of contemporary and historical treatment of MIBC is the underutilization of neo-adjuvant chemotherapy [8][9][10]. This underutilization exists despite the support of two randomized, phase III clinical trials.…”
Section: Introductionmentioning
confidence: 99%